2019
DOI: 10.1096/fj.201901626r
|View full text |Cite
|
Sign up to set email alerts
|

Fas‐apoptotic inhibitory molecule 2 localizes to the lysosome and facilitates autophagosome‐lysosome fusion through the LC3 interaction region motif–dependent interaction with LC3

Abstract: Abbreviations: BafA1, bafilomycin A1; BI-1, bax inhibitor-1; CASP, caspase; ER, endoplasmic reticulum; FAIM2, Fas-apoptotic inhibitory molecule 2; GABARAP, GABA type A receptor-associated protein; IDPR, intrinsically disordered protein region; LIR, LC3-interacting region; MAP1LC3B, microtubuleassociated protein 1 light chain 3 beta; MTOR, mammalian target of rapamycin; shRNA, small hairpin RNA; STX17, syntaxin 17; TMBIM, transmembrane BAX inhibitor motif containing. AbstractFas-apoptotic inhibitory molecule 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
(182 reference statements)
0
4
0
Order By: Relevance
“…In the prediction of sc2MeNetDrug, we also identified several important genes related to autophagy ( Fig 4F ). Some have already been shown to be related to neuron degeneration and autophagy in AD like FAIM2 [ 27 ], BCL2 [ 28 ], and PRNP [ 29 ]. One hypothesis is that irregular autophagy stimulation results in increased amyloid-β production [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the prediction of sc2MeNetDrug, we also identified several important genes related to autophagy ( Fig 4F ). Some have already been shown to be related to neuron degeneration and autophagy in AD like FAIM2 [ 27 ], BCL2 [ 28 ], and PRNP [ 29 ]. One hypothesis is that irregular autophagy stimulation results in increased amyloid-β production [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the prediction of sc2MeNetDrug, we also identified several important genes related to autophagy ( Fig 4f ). Some have already been shown to be related to neuron degeneration and autophagy in AD like FAIM2 35 , BCL2 36 , and PRNP 37 . One hypothesis is that irregular autophagy stimulation results in increased amyloid-β production 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Our cellular assay showed that LIR(p62) or LIR(FAIM2) preferentially bind to the lipidated forms of LC3 subfamily proteins rather than GABARAP subfamily proteins on autophagic membranes, although they bind to all or none of the mATG8s in the non-lipidated form, respectively (Figures 1 and S1B-S1G). It has been consistently reported that p62 binds to both LC3B and GABARAP-L2 in the cytosol but only to LC3B in autophagic membranes, whereas FAIM2 only binds to lipidated LC3B (LC3B-II) via the LIR motif using co-IP experiments in cells 33,34 . Why then do some LIR motifs show different binding properties to mATG8 depending on its localization?…”
Section: Discussionmentioning
confidence: 96%